Observation of interprofessional collaboration in primary care practice: A multiple case study. Issue 6 (1st November 2016) - Pullon, Susan; Morgan, Sonya; Macdonald, Lindsay; McKinlay, Eileen; Gray, Ben
ABSTRACT: Interprofessional collaboration (IPC) is known to improve and enhance care for people with complex healthcare and social care needs and is ideally anchored in primary care. Such care is complex, challenging, and often poorly undertaken. In countries such as Canada, the United Kingdom, the Netherlands, Australia, and New Zealand, primary care is provided predominantly via general practices, where groups of general practitioners and nurses typically work. Using a case study design, direct observations were made of interprofessional activity in three diverse general practices in New Zealand to determine how collaboration is achieved and maintained. Non-participant observation of health professional interaction was undertaken and recorded using field notes and video recordings. Observational data were subject to analysis prior to collection of interview data, subsequently gathered independently at each site. Case-specific themes were developed before determining cross-case themes. Cross-case themes revealed five key elements to IPC: the built environment, practice demographics and location, practice business models, shared goals, and team structure and climate. The combination of elements at each practice site indicated that strengths in one area helped offset challenges in others. The three practices (cases) collectively demonstrated the importance of an "all of practice" commitment to collaborative practice so that shared decision-making can occur.